The Influence of the STAD Type Cooperative Learning Model Assisted by Canva on the Motivation and Creativity of Grade VI Students at SDN 21 Bengkalis - Ujiyanto; Nurmalina; Ramdhan witarsa (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study applied the Student Teams Achievement Division (STAD) cooperative learning model assisted by Canva to 32 sixth grade students of SDN 21 Bengkalis. Data on students' learning motivation and creativity were obtained through pretest and posttest questionnaires. This study aims to determine the effect of using the Student Teams Achievement Division (STAD) cooperative learning model assisted by Canva on the motivation and creativity of sixth grade students of SDN 21 Bengkalis. The results of the analysis showed a significant increase in the average score of learning motivation from 23.41 in the pretest to 32.59 in the posttest, and the average score of creativity from 16.78 in the pretest to 28.78 in the posttest. The Shapiro-Wilk normality test confirmed that the data were normally distributed, and the paired t-test showed a significant effect of the STAD cooperative learning model assisted by Canva on students' motivation (Sig. <0.001) and creativity (Sig. <0.001). The implementation of this learning model involves the stages of delivering objectives and motivation, group division, teacher presentations, group work, quizzes, and team awards and presentations. In conclusion, the STAD type cooperative learning model assisted by Canva has proven effective in increasing the motivation and creativity of sixth grade students at SDN 21 Bengkalis